Case Report: Neuromyelitis Optica Spectrum Disorder With Progressive Elevation of Cerebrospinal Fluid Cell Count and Protein Level Mimicking Infectious Meningomyelitis: A Diagnostic Challenge - Zhang, Yin-Xi; Cai, Meng-Ting; He, Ming-Xia; Lu, Yu-Qiang; Luo, Xiao; Zhang, Tian-Yi (Frontiers in Immunology, 2022)
Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune-mediated idiopathic inflammatory demyelinating disease with typical clinical presentation of optic neuritis, acute myelitis and area postrema syndrome. Most NMOSD patients are seropositive for disease-specific and pathogenic aquaporin-4 (AQP4) antibodies, which are key markers for the NMOSD diagnosis. Herein, we report an atypical case of a 41-year-old male, who complained of intractable hiccups and vomiting at disease onset, followed by fever, headache, back pain, progressive paresthesia and weakness of extremities later on. Magnetic resonance imaging revealed longitudinally extensive transverse myelitis. Cerebrospinal fluid analysis showed progressive increases in the white cell count and the protein level, which were accompanied by the deterioration of clinical manifestations. The patient was initially suspected of infectious meningomyelitis but was finally diagnosed with NMOSD. This case with distinct cerebrospinal fluid findings broadens the phenotypic spectrum of NMOSD. Furthermore, it also highlights the clinical value of AQP4 antibody test for early definite diagnosis and proper treatment.